The Role of Clock Genes in Fibrinolysis Regulation: Circadian Disturbance and Its Effect on Fibrinolytic Activity - Carmona, Pamela; Mendez, Natalia; Ili, Carmen G.; Brebi, Priscilla (Frontiers in Physiology, 2020)
The fibrinolytic system is critical during the onset of fibrinolysis, a fundamental mechanism for fibrin degradation. Both, tissue plasminogen activator (tPA) and urokinase plasminogen activator (uPA) triggers fibrinolysis, leading to proteolytic activation of plasminogen to plasmin and subsequently fibrin proteolysis. This system is regulated by several inhibitors; plasminogen activator inhibitor 1 (PAI-1) the most studied, binds to and inactivates both, tPA and uPA. Through the action of plasmin, this system regulates several physiological processes: embryogenesis, activation of inflammatory cells, cell proliferation and death, synaptic plasticity, wound healing and others. The deregulated intervention of fibrinolysis in the pathophysiology of various diseases has been widely studied; findings of altered functioning have been reported in different chronic non-communicable diseases (NCD), reinforcing its pleiotropic character and the importance of its physiology and regulation. The evidence indicates that fundamental elements of the fibrinolytic system, such as tPA and PAI-1, show a circadian rhythm in their plasmatic levels and their gene expression are regulated by circadian system elements, known as clock genes - Bmal, Clock, Cry- and accessory clock genes such as Rev-Erb and Ror. The disturbance in the molecular machinery of the clock by exposure to light during the night alters the natural light/dark cycle and causing disruption of the circadian rhythm. Such exposure affects the synchronization and functioning of peripheral clocks responsible for the expression of the components of the fibrinolytic system. So, this circadian disturbance could be critical in the pathophysiology of chronic diseases where this system has been found to be deregulated.